Genome and Transcriptome Analysis of A. baumannii's "Transient" Increase in Drug Resistance under Tigecycline Pressure. (September 2020) - Cheng, Jianjun; Kesavan, Dinesh Kumar; Vasudevan, Aparna; Cai, Wei; Wang, Huixuan; Su, Zhaoliang; Wang, Shengjun; Xu, Huaxi
Highlights: Completed the process of drug resistance enhancement and recovery of Acinetobacter baumannii in vitro, further understanding the phenomenon of drug resistance. The combination of genomic and transcriptome methods has comprehensively revealed the possible reasons for the increased resistance of specific Acinetobacter baumannii under tigecycline pressure. Abstract: Objectives: As a common nosocomial infection bacterium, A. baumannii 's drug resistance rate continues to rise. In this study, the objective was to explore the possible reasons for the increased drug resistance of A. baumannii after tigecycline treatment. Methods: Based on the drug resistance analysis of 183 clinical isolates of A. baumannii, a pair of strains (AB711 and AB721) which changed their resistance after treatment was selected. Tigecycline was used to induce the drug resistance of strain AB711 in vitro. The differential expressed genes from A. baumannii strains were analyzed using whole gene sequencing (WGS) and RNA sequencing (RNA-seq) combined with online MLST, SNP tools and bioinformatics software, and verified by reverse transcription quantitative polymerase chain reaction (RT-qPCR). Results: AB721 became more resistant to tetracyclines than AB711 at the initial detection. However, after a period of time, the resistance of AB711 and AB721 became consistent. This phenomenon can also be repeated using AB711 in vitro. After induction, the AB711 with increased MIC value of tigecycline was named AB712. The results of WGS, MLST and SNP based Phylogenetic tree indicated that AB711, AB712, AB721 were co-origin and belong to ST2 (Pasteur) / ST1791 (Oxford). Comparative transcriptome indicated that the Differential expression of some genes can play an important role in the resistance enhancement process of AB711. For example, compared with AB711, genes related to benzene-containing compound metabolic process, translation, ribosomal structure and biogenesis and so on were upregulated significantly in AB712. In addition, efflux pumps such as RND transporter permease subunit, EmrAB, MacB, and Tet resistance operon were also upregulated. Conclusion: Tigcycline induced changes in the expression of some related genes in A. baumannii, which may be the main reason for its increased drug resistance.